Co-designing adult weight management services: a qualitative study exploring barriers, facilitators, and considerations for future commissioning - Rebecca Langford; Rowan Brockman; Jonathan Banks; Russell Jago; Fiona Gillison; Karen Coulman; Theresa Moore; James Nobles (BMC Public Health, 2024)
Abstract Background Weight management services have not always benefitted everyone equally. People who live in more deprived areas, racially minoritised communities, those with complex additional needs (e.g., a physical or mental disability), and men are less likely to take part in weight management services. This can subsequently widen health inequalities. One way to counter this is to co-design services with under-served groups to better meet their needs. Using a case study approach, we explored how co-designed adult weight management services were developed, the barriers and facilitators to co-design, and the implications for future commissioning. Methods We selected four case studies of adult weight management services in Southwest England where co-design had been planned, representing a range of populations and settings. In each case, we recruited commissioners and providers of the services, and where possible, community members involved in co-design activities. Interviews were conducted online, audio-recorded, transcribed verbatim, and analysed using thematic analysis. Results We interviewed 18 participants (8 female; 10 male): seven commissioners, eight providers, and three community members involved in co-designing the services. The case studies used a range of co-design activities (planned and actualised), from light-touch to more in-depth approaches. In two case studies, co-design activities were planned but were not fully implemented due to organisational time or funding constraints. Co-design was viewed positively by participants as a way of creating more appropriate services and better engagement, thus potentially leading to reduced inequalities. Building relationships– with communities, individual community members, and with partner organisations– was critical for successful co-design and took time and effort. Short-term and unpredictable funding often hindered co-design efforts and could damage relationships with communities. Some commissioners raised concerns over the limited evidence for co-design, while others described having to embrace “a different way of thinking” when commissioning for co-design. Conclusions Co-design is an increasingly popular approach to designing health in services but can be difficult to achieve within traditional funding and commissioning practices. Drawing on our case studies, we present key considerations for those wanting to co-design health services, noting the importance of building strong relationships, creating supportive organisational cultures, and developing the evidence base.